2018
DOI: 10.1007/s11721-018-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Local information-based control for probabilistic swarm distribution guidance

Abstract: This paper addresses a task allocation problem for a large-scale robotic swarm, namely swarm distribution guidance problem. Unlike most of the existing frameworks handling this problem, the proposed framework suggests utilising local information available to generate its time-varying stochastic policies. As each agent requires only local consistency on information with neighbouring agents, rather than the global consistency, the proposed framework offers various advantages, e.g., a shorter timescale for using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…An important feature of this LICA-based method is that using local information only, and enables an asynchronous implementation. Algorithms for Markov chain synthesis under flux upper limits, and, for local information based quorum model are also reported by Jang et al [30].…”
Section: Local Information Consistency -Inhomogeneous Markov Chainsmentioning
confidence: 76%
See 2 more Smart Citations
“…An important feature of this LICA-based method is that using local information only, and enables an asynchronous implementation. Algorithms for Markov chain synthesis under flux upper limits, and, for local information based quorum model are also reported by Jang et al [30].…”
Section: Local Information Consistency -Inhomogeneous Markov Chainsmentioning
confidence: 76%
“…Task allocation is used to drive the speed distribution of vehicles to the desired distribution and maintain it. The methods used for task allocation are based on homogeneous Markov chains (HMC [28]), inhomogeneous Markov chains (IMC [29]) and inhomogeneous Markov chains using local information only (LICA IMC [30]).…”
Section: Focus Of the Papermentioning
confidence: 99%
See 1 more Smart Citation
“…We note that it is possible to realize a decentralized implementation of the proposed optimization problem in ( 34)-(39). Indeed, prior work has demonstrated that one can compute the state information X locally, and enable online adaptation (re-optimization) of the transition rates as the state information is updated [3,15,24,28]. Our approach, while introducing new capabilities, directly inherits these advantages from prior work.…”
Section: Decentralized Online Implementationmentioning
confidence: 97%
“…Furthermore, the covariance between any two elements of Y is given by Example The expected value of the species-trait matrix and the initial abstract state information of our example problem are defined in ( 6) and ( 7), respectively. Thus, the expected values of the initial trait distribution and the associated variances can be computed using (14) and (15), and are thus given by…”
Section: Trait Aggregation and Distributionmentioning
confidence: 99%